Characterization of a porin from the outer membrane of Vibrio anguillarum. - Simón, M (1996)
The outer membranes of the 10 serovars of Vibrio anguillarum showed a common major protein with a size of around 40 kDa. Antibodies against the major outer membrane protein (MOMP) of V. anguillarum AO18 (serovar O1) cross-reacted with the MOMPs of all the other serovars but not with the outer membrane proteins of Escherichia coli. The MOMP of V. anguillarum serovar O1 was isolated, reconstituted to two-dimensional crystals, and structurally characterized by electron microscopy and image processing. The unit cell structure of the crystalline MOMP, as well as the secondary structure composition of the protein with a high amount of beta-structure, is strongly reminiscent of that of bacterial porins. The functional properties of the pores were investigated by conductance measurements with the MOMP reconstituted in planar lipid membranes. The V. anguillarum MOMP is characterized by a relatively weak cation selectivity and a moderate surface charge, and it shows voltage-dependent conductance effects. The MOMP is functionally similar to OmpF from E. coli, and it can be classified as a general diffusion porin.